Tracing Virtual Reality Research: A 2009–2024 Bibliometric Analysis - Desi Handayani (Journal of Technology-Assisted Learning, 2025)
This study provides a comprehensive bibliometric analysis of virtual reality (VR) research in education from 2009 to 2024, with data sourced from the Scopus database. Out of 1,749 initial publications, a refined selection of 735 articles was analyzed using Bibliometrix software. Results reveal significant growth in VR research, particularly in K-12 and higher education, with peak citations observed in 2014. The United States and China emerged as leading contributors, producing the most impactful studies. Central research themes focus on VR’s role in enhancing instructional design through games, simulations, and immersive environments. The analysis identifies influential authors and institutions, with Hwang G.J. as the top author and National Taiwan Normal University leading in institutional contributions. The most cited articles highlight VR’s efficacy in improving student engagement, comprehension of abstract concepts, and overall learning outcomes. A notable finding is the application of VR in collaborative and experiential learning, as well as its potential to address educational needs for diverse learners, including those with disabilities. Key bibliometric indicators underscore a 20.68% annual growth rate in publications, with interdisciplinary collaboration playing a pivotal role. Visualization through citation and co-citation networks elucidates the intellectual structure of VR research, highlighting prominent studies and emerging trends. Keywords like “virtual reality,” “e-learning,” and “students” dominate, reflecting a focus on technology-driven educational methods. This research provides valuable insights into the evolving landscape of VR in education, emphasizing its transformative potential. It informs educators, policymakers, and researchers on the trends, challenges, and opportunities for integrating VR technologies into educational practices to enhance learning experiences and outcomes.